Sejarah Dan Profil Gereja Keluarga Tabgha Alma Jaya Malaysia: Peristiwa Sejarah masuk dan berkembangnya Gereja Keluarga Tabgha Alma Jaya di Malaysia - George Rudi Hartono Pasaribu; Steven; Robertus Suryadi (JURNAL IMPARTA, 2023)
This study aims to describe the history and profile of the Tabgha Family Church Alma Jaya in Malaysia, the background before starting church planting in Malaysia, building partnerships with local churches until the formation of the Tabgha Family Church Alma Jaya. The method used in this study is a qualitative approach, using the snowball technique with heuristic steps through observation, interviews, study of documents and determination of informants, data analysis, field observations, interviews with witnesses and historical actors, and focus group discussions. Data analysis by interpreting documents and information obtained in the field. Interpretation and discussion in the form of a description. The results of the data analysis show that the early entry of the Tabgha Family Church was born from a vision received by Pdt. Hanny Andries during a prayer and fasting movement for two years, from 1998 to 2000, the entry and development of the Tabgha Alma Jaya Family Church applied the model of cooperation with the local church with the characteristic of building friendship. The pattern of approach that stands out in outreach is to make the congregation feel at home and part of the family. The characteristics of the ministry of the Tabgha Alma Jaya Family Church are Prayer Strengthening, Worship Praise and the development of cell groups and the empowerment of the lay congregation.